On plastic anisotropy and deformation history-driven anelasticity of an extruded magnesium alloy. (February 2020) - Wang, Huai; Lee, Soo Yeol; Wang, Huamiao; Woo, Wanchuck; Huang, E-Wen; Jain, Jayant; An, Ke
Abstract: The plastic anisotropy and unloading anelasticity of an extruded Mg-9 wt.%Al alloy (with two annealed textures) were investigated using in-situ neutron diffraction measurement and crystal plasticity modelling. The distinctive yielding and hardening behaviors during compressive and tensile loading-unloading cycles were interpreted by the alternative operations of different slip/twinning modes. We reveal that the micromechanical responses of differently-oriented grains strongly depend on their neighboring conditions and operative deformation mechanisms. Based on the modelling results, unloading anelasticity is hypothesized to be controlled by the plastic contribution of the hard deformation mode and its impeding effects on easier deformation modes. Graphical abstract: Image, graphical abstract